Pengaruh Islam terhadap Budaya Kerja Suku Sasak - Muhasim Muhasim (LP2M STIT Palapa Nusantara, 2016)
Lombok Island, the island in 1000 (one thousand) mosque, which is the place of domicile sasak, which is majority Muslim. Islam is meant here is based on the creed of monotheism, Shari'a and morals, with sincerity, priests and science. Islam is the doctrine of truth that comes from God the Creator, except that there is an act of culture and human behavior. Therefore, Islam and culture are two different sides, and may influence each other. Culture sasak unique and different than the culture of 1,300 -suku tribal cultures that exist in Indonesia. No wonder many kumunitas complaining sasak culture, there is an opinion similar to the culture of Balinese or Javanese tribe, but all including the culture of Indonesia. This report explores the influence of Islam teradap sasak work culture, using descriptive method, so it can be viewed in a straightforward and cultural influences sasak both from the application of Islamic values, cultural traits sasak and the influence of the teachings of Islam to the formation of the work culture. The influence can be negative, such as a misguided understanding of the teachings and values of Islam, the rise of terrorism, Kekeran among fellow citizens, and between religions, but in this article is meant to influence is the nature pesitif that is affecting a culture of co sasak based values of Islam. The problem is there are parties in the name of Islam, but the way, his behavior is wrong, such as terrorism, the Kekeran between Warg and inter-religious, it is not the true teachings of Islam and not the intended human culture. Faith in Islam can grow, can also be reduced, can be strong, very strong, can be weak, very weak, could even disappear alias be hypocritical. It could be any identity as followers of Islam, but the attitude, the nature, behavior and culture, away from the teachings of Islam, such as terrorism and acts of violence. This article could be a solution to the problem at hand, evoke memories of fellow citizens so it stays on the right track according to religious teachings. Provide motivation, innovation and foster creativity work, which has positive influence on the culture of the working people, especially susku sasak, which 22 not only sasak that berdommisili in Lombok, but wherever domiciled, whether as a power Transimigrasi or who are into the workforce in the neighboring country.